2018
DOI: 10.3390/nu10030374
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Perceptions of Toddler Beverages

Abstract: Background: The prevalence of obesity among Australian pre-school children is a major concern with links to poor health outcomes. One contributing factor is excess energy intake. Sugar-sweetened beverages are energy-dense, nutrient-poor, readily available and have been implicated in the increasing prevalence of obesity. Furthermore, preschooler beverage consumption may develop into dietary habits that track into adulthood. There is little research on factors influencing parents’ decision-making when serving be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…One reason that caregivers may inappropriately serve toddler milk to infants and infant formula to toddlers could be due to confusion about the appropriate ages to serve each product and/or difficulty in distinguishing between the two categories, as identified in this research and previous qualitative studies (N. Berry et al, 2010; N. J. Berry, Jones, & Iverson, 2012;Rigo, Willcox, Spence, & Worsley, 2018). The FDA should establish a common name for toddler milks (i.e., statement of identity) and require that toddler milk labels clearly state the appropriate ages for the product and that they are not substitutes for infant formula (Pomeranz et al, 2018).…”
Section: Opportunities For Public Health Policymentioning
confidence: 77%
“…One reason that caregivers may inappropriately serve toddler milk to infants and infant formula to toddlers could be due to confusion about the appropriate ages to serve each product and/or difficulty in distinguishing between the two categories, as identified in this research and previous qualitative studies (N. Berry et al, 2010; N. J. Berry, Jones, & Iverson, 2012;Rigo, Willcox, Spence, & Worsley, 2018). The FDA should establish a common name for toddler milks (i.e., statement of identity) and require that toddler milk labels clearly state the appropriate ages for the product and that they are not substitutes for infant formula (Pomeranz et al, 2018).…”
Section: Opportunities For Public Health Policymentioning
confidence: 77%
“…9,11,12 Research has shown that this marketing misleads consumers. [13][14][15][16][17][18] In a 2022 study, 18 parents who viewed fruit drinks with claims were more likely to incorrectly believe that these products did not contain added sugar or were 100% juice. Correcting these misperceptions could enhance parents' knowledge and encourage healthier beverage purchases.…”
Section: Introductionmentioning
confidence: 99%
“…Several research papers analyse the behaviour of children in supermarkets and discuss it as a health-problem. For the purposes of boosting the sales of the Orange Bubble Juice, this confirms that the parents of the children in the target group are likely to succumb to the tantrum, as in e.g., O’Dougherty et al (2006); Maubach et al (2009) , Carnell et al (2011) ; Henry and Borzekowski (2011) , Lesser et al (2012) ; Swinburn et al (2013) , Winston et al (2013) ; Haselhoff et al (2014) , Mason et al (2014) ; Tipton (2014) , and Rigo et al (2018) . For the placement strategy, in general, the diversity of product availability has broadened exponentially in the past decades, making choices effortful.…”
Section: Introductionmentioning
confidence: 56%
“…Regarding individual health, the product’s chemical composition (product design) induces children to ingest more sugar than what is healthy ( Harris et al, 2015 ). As is well-known, the building blocks of adult obesity are set in childhood ( Longacre et al, 2016 ; Hartmann et al, 2017 ; Rigo et al, 2018 ), and dental health is among the most painful and immediate consequences of surplus sugar ingestion ( Duijster et al, 2015 ; Mela and Woolner, 2018 ).…”
Section: Introductionmentioning
confidence: 99%